Ethical aspects of health and wellbeing of young elite athletes : conceptual and normative issues - Zurc, Joca (Array, 2020)
Sport and physical activities offer a sensitive environment where the values of humanity, human rights, empathy and fair play come to the fore. However, at the same time the competition nature of sport and the interest of winning at any cost represent a risks of harm, especially for young preadolescent athletes. Therefore, the need arises to identify the main ethical conceptual and normative issues of the top youth sport. Our critical review of possible risk factors and empirical findings of semi structured in-depth interviews with four top-level gymnastics’ coaches showed that achievements of children in sport are the result of multiple factors driven by the main force of the ethics of maximum behind. Gymnasts’ intrinsic motivation, pleasure to sport, persistent hard work, start at early age, and the role of parents are essential for success. However, the morality of the coach as a reflection of society values should be carefully considered in the future.